Commendable Attitudes And Deeds As A Condition For Commutation Of The Death Penalty Perspective Q.S. Al-Maidah (5): 33-34 - Suci Hidayati Malau; Noor Azizah (UNIVERSITAS PAKUAN, 2026)
Article 100 of Law Number 1 of 2023 concerning the Criminal Code makes